Awareness of male infertility among the medical students in Udayana University of batch 2015 - Omprakash Nanda Kumar; Yuliana Yuliana; I Nyoman Mangku Karmaya (DiscoverSys Inc., 2020)
Background: Infertility is defined as the inability to conceive after one year of unprotected sex which was affected eighty million people all over the world. Male infertility is involved in approximately 40% of the more than 2 million infertile married couples in the United States. Health promotion strategies are therefore recommended to begin with educational interventions to increased knowledge of infertility awareness. University years are a time for self-maturation which includes sexual exploration and pregnancy avoidance during this life-course transition to adulthood. There’s still no data about the awareness and knowledge about male infertility among university student especially medical student in Indonesia.Aim: The study aims to know the level awareness on male infertility among the medical students in Udayana University of batch 2015.Methods: This study was a descriptive cross-sectional design conducted on June 2018. The subjects were 102 medical students from regular and international class of Faculty of Medicine, Udayana University. The data derived with questionnaires and a preceding informed consent already had been gained from all the participants.Results: Most of the subjects were belong to the somewhat knowledgeable group (41.2%). English class and female students had the better awareness regarding the male infertility issue (36.8% and 46.7%). The highest percentages of correct answered subtheme questions were diagnosis (55%) subtheme.Conclusion: Infertility awareness, including knowledge of male risk factors, is a critical first step towards fertility preservation through lifestyle modification.